Nucleus accumbens shell and core dopamine responsiveness to sucrose in rats: role of response contingency and discriminative/conditioned cues. (3rd February 2015) - Bassareo, V.; Cucca, F.; Musio, P.; Lecca, D.; Frau, R.; Di Chiara, G.
Abstract: This study investigated by microdialysis the role of response contingency and food‐associated cues in the responsiveness of dopamine transmission in the nucleus accumbens shell and core to sucrose feeding. In naive rats, single‐trial non‐contingent presentation and feeding of sucrose pellets increased dialysate shell dopamine and induced full habituation of dopamine responsiveness to sucrose feeding 24 and 48 h later. In rats trained to respond for sucrose pellets on a fixed ratio 1 (FR1) schedule, dialysate dopamine increased in the shell but not in the core during active responding as well as under extinction in the presence of sucrose cues. In rats yoked to the operant rats, the presentation of sucrose cues also increased dialysate dopamine selectively in the shell. In contrast, non‐contingent sucrose presentation and feeding in FR1‐trained and in yoked rats increased dialysate dopamine to a similar extent in the shell and core. It is concluded that, whereas non‐contingent sucrose feeding activated dopamine transmission in the shell and core, response‐contingent feeding activated, without habituation, dopamine transmission selectively in the shell as a result of the action of sucrose conditioned cues. These observations are consistent with a critical role of conditioned cues acquired during training and differential activation of shell vs. core dopamine for response‐contingent sucrose feeding. Abstract : The main goal of this study was to investigate the role of sucrose‐related cues and response contingency in the responsiveness of NAc shell and core DA transmission. Learning of responding for sucrose involves build‐up of activation of shell and suppression of core dopamine responsiveness. This apparent loss of habituation of shell dopamine under response contingent sucrose feeding might involve a shift from primary to conditioned stimuli as determinants of accumbens shell dopamine activation.